Three‐Dimensional Echocardiography and 2D‐3D Speckle‐Tracking Imaging in Chronic Pulmonary Hypertension: Diagnostic Accuracy in Detecting Hemodynamic Signs of Right Ventricular (RV) Failure. Issue 3 (March 2015) - Vitarelli, Antonio; Mangieri, Enrico; Terzano, Claudio; Gaudio, Carlo; Salsano, Felice; Rosato, Edoardo; Capotosto, Lidia; D'Orazio, Simona; Azzano, Alessia; Truscelli, Giovanni; Cocco, Nino; Ashurov, Rasul
Abstract : Background: Our aim was to compare three‐dimensional (3D) and 2D and 3D speckle‐tracking (2D‐STE, 3D‐STE) echocardiographic parameters with conventional right ventricular (RV) indexes in patients with chronic pulmonary hypertension (PH), and investigate whether these techniques could result in better correlation with hemodynamic variables indicative of heart failure. Methods and Results: Seventy‐three adult patients (mean age, 53±13 years; 44% male) with chronic PH of different etiologies were studied by echocardiography and cardiac catheterization (25 precapillary PH from pulmonary arterial hypertension, 23 obstructive pulmonary heart disease, and 23 postcapillary PH from mitral regurgitation). Thirty healthy subjects (mean age, 54±15 years; 43% male) served as controls. Standard 2D measurements (RV–fractional area change–tricuspid annular plane systolic excursion) and mitral and tricuspid tissue Doppler annular velocities were obtained. RV 3D volumes and global and regional ejection fraction (3D‐RVEF) were determined. RV strains were calculated by 2D‐STE and 3D‐STE. RV 3D global‐free‐wall longitudinal strain (3DGFW‐RVLS), 2D global‐free‐wall longitudinal strain (GFW‐RVLS), apical‐free‐wall longitudinal strain, basal‐free‐wall longitudinal strain, and 3D‐RVEF were lower in patients with precapillary PH ( P <0.0001) and postcapillary PH ( P <0.01) compared to controls. 3DGFW‐RVLS (hazard ratio 4.6, 95% CI 2.79 to 8.38, P =0.004) and 3D‐RVEF (hazard ratio 5.3, 95% CI 2.85 to 9.89, P =0.002) were independent predictors of mortality. Receiver operating characteristic curves showed that the thresholds offering an adequate compromise between sensitivity and specificity for detecting hemodynamic signs of RV failure were 39% for 3D‐RVEF (AUC 0.89), −17% for 3DGFW‐RVLS (AUC 0.88), −18% for GFW‐RVLS (AUC 0.88), −16% for apical‐free‐wall longitudinal strain (AUC 0.85), 16 mm for tricuspid annular plane systolic excursion (AUC 0.67), and 38% for RV‐FAC (AUC 0.62). Conclusions: In chronic PH, 3D, 2D‐STE and 3D‐STE parameters indicate global and regional RV dysfunction that is associated with RV failure hemodynamics better than conventional echo indices.